The mediation relationship of customer satisfaction between service quality and repurchase intention on e-commerce in Indonesia - Aida Sari; Dwi Asri Siti Ambarwati; Mudji Rachmat Ramelan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
This research aims to determine the relationship between service qualities and repurchase intention with customer satisfaction as the mediator variable on e-commerce in Indonesia. Data were obtained from 162 respondents by using close and self-administered types of questions. The respondents independently filled the given questionnaires with the Likert scale and Structural Equation Model (SEM) was used for analysis. The findings show that customer satisfaction variable is a mediation of web service quality and repurchase intention on e-commerce in Indonesia.